Fe2CS2 MXene: a promising electrode for Al-ion batteries. Issue 9 (21st February 2020) - Lee, Sangjin; Jung, Sung Chul; Han, Young-Kyu
Abstract : Using late transition metals and sulfur termination groups for MXene leads to 10 4 -fold increase in Al-ion transport and 2.2-fold increase in Al-ion capacity, respectively. Abstract : Aluminum-ion batteries are one of the most promising candidates for next-generation rechargeable batteries. However, the strong electrostatic interactions between highly ionic Al 3+ and the electrode hinder the reversible intercalation and fast transport of Al ions. This study suggests a design strategy for a MXene electrode for realizing high-performance Al-ion batteries. Instead of early transition metals and oxygen, the metal M and surface termination T of general MXene (M n +1 X n T x ), the use of late transition metals and sulfur can dramatically improve the capacity and rate capability, respectively. The capacity increases 2.2-fold, from 288 mA h g −1 (Ti2 CO2 ) to 642 mA h g −1 (Fe2 CS2 ), and the Al-ion diffusivity increases 10 4 -fold, from 2.8 × 10 −16 cm 2 s −1 (Ti2 CO2 ) to 6.0 × 10 −12 cm 2 s −1 (Fe2 CS2 ). This remarkable performance enhancement is due to the charge redistribution in the M and T layers by the late transition metals and the shallowing of the potential energy surface for Al-ion intercalation by sulfur.